FRAILTY-FREE LIFE EXPECTANCY IN OLDER MEXICAN AMERICANS. (11th November 2018) - Al Snih, S; Chen, N; Eschbach, K; Markides, K; Ottenbacher, K
Abstract: The objective of this study was to examine the total life expectancy (TLE), frailty-free life expectancy (FFLE), frailty life expectancy (FLE), pre-frailty life expectancy (PFLE), and frailty free-disability life expectancy. Data are from an 18-year prospective cohort study of 2438 non-institutionalized Mexican American aged 67 years and older from the Hispanic Established Population for the Epidemiological Study of the Elderly (1995/96–2004/05). Frailty was defined as meeting two or more of the following: unintentional weight loss of > 10 pounds, weakness, self-reported exhaustion, and slow walking speed. Total life expectancy and frailty-free life expectancy were estimated using the interpolation of Markov chain method. At baseline, 54.4% participants were non-frail, 32.8% were pre-frail, and 15.8% were frail. For men, the TLE at age 67 was 15.5 years, the FFLE was 6.5 years, the PFLE was 5.4 years, and the FLE was 3.6 years. For women, the TLE at age 67 was 17.5 years, the FFLE was 6.5 years, the PFLE was 6.5 years, and the FLE was 4.5 years. For men, frailty free-disability LE was 2.7 years and with disability was 1.1 years. For women, frailty free-disability LE was 2.5 years and with disability was 2.1 years. For men, pre-frailty free-disability LE was 5.1 years and with disability was 0.4 years. For women, pre-frailty free-disability LE was 6.0 years and with disability was 0.8 years. This study showed that at every age, women had fewer years in non-frailty state and more years of LE in pre-frail state, frail state, and with disability.